Peranan Influencer Game Valorant Terhadap Minat Beli dan Keputusan Pembelian Produk Valorant di Komunitas Valorant Indonesia - Hasibuan, Rayhan (Program Studi Ilmu Administrasi Bisnis FISIP UNPAS, 2024)
Online gaming has shown significant and promising growth. One example of an online game is Valorant. Valorant is experiencing a rapid increase in new players and active players, according to reports from August 2022, where there was an average of 21 million players in March, with 1.5 million players active daily. Additionally, there has been an increase in Content Creation aspects, such as the number of influencers and revenue. Based on this phenomenon, many Valorant Game Influencers provide reviews and recommendations for Valorant Game products. In a study titled